Prevalence of cardiac dysfunction in type 2 diabetes in a tertiary health care setup - Nakkina, Bhavani Prasad; Narukurthi , Ravi Kiran; Bhaskar, D; T, Jaya Chandra (International Journal of Medical Research and Review, 2019)
Introduction: Diabetes mellitus (DM) may be one factor that specifically influences cardiac diastolic function. The present study was designed to examine cardiac dysfunction in diabetes subjects with non-chronic renal failure (CRF). Materials and methods: Study was approved by Institutional ethics committee, Informed consent from the study subjects. Diagnosis of diabetes was made according to WHO criteria. Plasma glucose concentration, serum lipids (total cholesterol, triglycerides, LDL cholesterol and HDL plasma cholesterol concentrations) were measured as per standard procedures. Glycosylated hemoglobin (HbA1c) was estimated by ion exchange resin method. ECG recording was obtained for every subject to rule out ischemic heart disease. Results: Of the 150 study Type 2 diabetes participants, the male female ratio was 1.1. The mean HbA1C was 9.112±1.36 %. 2D ECHO findings showed 34% left ventricular hypertrophy and 51.3% diastolic dysfunction. Dyslipidemia was identified in 54.7% and statistically there was no significant association between dyslipidemia and diastolic dysfunction (P = 0.532). Conclusion: In this study, diastolic dysfunction dyslipidemia was identified in 51.5% participants without dyslipedemia. Though, there was no significant difference, this number is to be considered. However, studies should be conducted with big samples size.